FLOWERING AND FRUITING CYCLE OF Cinnamomum sintoc Blume IN LOWLAND FOREST OF CIREMAI MOUNTAIN NATIONAL PARK, WEST JAVA AND THE IMPLICATION FOR CONSERVATION - AGUS YADI ISMAIL AGUS YADI ISMAIL; Toto Supartono; Agung Rifai; Eming Sudiana; Elly Proklamasiningsih (Media Konservasi, 2022)
Cinnamomum sintoc Blume is an endangered species experiencing an ongoing decline due to overharvesting; in- and ex-situ conservation efforts are urgently needed to ensure its survival. We performed a detailed assessment of the flowering and fruiting phenology of C. sintoc in a lowland forest in West Java, Indonesia. We aimed to relate the duration of each phenological phase to environmental factors including elevation, humidity, temperature, and slope, as well as the orientation of the flowers. A total of 30 trees were sampled from three elevation ranges (500–700, 700–900, and 900–1,100 m). We found that C. sintoc requires approximately 40 days to complete flowering and an additional 82 days to produce mature fruit. The period from flower initiation to fruit ripening spans 4 months, from late July to early November. Flowers that are east-facing developed mature fruit more rapidly than those facing other directions, and the shortest flowering and fruiting phenological period was observed for east-facing flowers at 700–900 m. These results provide a baseline for studying phenological shifts in C. sintoc, and could inform seed harvesting efforts for conservation projects in the study area of Gunung Cermai National Park. Key words: Bintangkot, declining population, Endangered species, Lauraceae, phenology